Determining COVID-19 disease severity and outcome using sequential chest radiograph in a new designated COVID-19 hospital - Munirathnam, Mahendra; C. N., Mohan; Mohammadi, Javeriya; Gowda, Samarth S.; Ramaiah, Madhumati (International Journal of Advances in Medicine, 2020)
Background: COVID-19 pandemic to date has recorded around 37 million cases across the world. This study was done to appraise the prognostic importance of portable chest X-ray (CXR) and the Brixia scoring was then used to predict the outcome variables like hypoxia, non-invasive ventilation, intubation, sepsis, multiple organ dysfunction syndrome (MODS), recovery, death and post corona sequalae. Methods: A 100 reverse transcriptase-polymerase chain reaction (RT-PCR) confirmed COVID-19 infection were included in the study, based on the inclusion and exclusion criteria. A CXR was done on admission and on day 3 following admission. The CXR Brixia score was calculated and was correlated with lab parameters, hypoxia, need for mechanical ventilator and clinical outcome variables. P value of <0.05 was taken as significant. Results: The mean Brixia score on admission were 2.52±1.505, 6.18±2.969 and 12.05±3.251 in mild, moderate and severe category respectively and the scores that were calculated 3 days after admission were 2.52±1.505, 6.18±2.969 and 12.14±3.306 in mild, moderate and severe category respectively, it was found that mean Brixia scores were higher in patients with moderate and severe category compared to mild category. There was a statistically significant correlation between lymphopenia, lactate dehydrogenase (LDH), d-dimer, C-reactive protein (CRP) and serum ferritin with Brixia score on admission. Conclusions: The simple and a bedside Brixia CXR score has shown that the higher scores predict a need for monitoring and management to prevent poor clinical outcome and mitigate complications and death. When this score is used along with other easily available biochemical parameters is useful in predicting clinical outcome and prognosis.